RAPID MAGNITUDE ESTIMATION OF 2019 M6.9 BANTEN EARTHQUAKE USING GNSS 1HZ - Ongky Anggara; Novia Rohmadona; Redho Surya Perdana; Satrio Muhammad Alif; Een Lujainatul Isnaini; Muhammad Al Kautsar (GeoEco, 2026)
Rapid magnitude estimation remains challenging in Indonesia due to the limited evaluation of high-rate Global Navigation Satellite System (GNSS) data and the lack of region-specific validation of existing Peak Ground Displacement (PGD) scaling relations for earthquake early warning applications. This study investigates the performance of high-rate GNSS data (1 Hz) for rapid magnitude estimation of the August 2 2019, Banten earthquake (Mw 6.9). Using 15 InaCORS stations provided by the Geospatial Information Agency of Indonesia, the data were processed using Precise Point Positioning with Ambiguity Resolution (PPP-AR). PGD values were extracted and applied to three empirical scaling relations proposed by Melgar et al. (2015), Crowell et al. (2016), and Ruhl et al. (2019). This study presents a comparative evaluation of multiple PGD scaling models using real Indonesian GNSS data, providing insight into their performance in a tectonic setting that remains underrepresented in previous studies. The results show that all models successfully converged to Mw 6.9, with convergence times ranging from 20 to 160 seconds after the earthquake origin time. However, this study is limited by the analysis of a single earthquake event and the use of global scaling relations that are not specifically calibrated for Indonesian tectonic conditions. These findings demonstrate the potential of high-rate GNSS as a complementary tool to seismic sensors for rapid magnitude estimation. The integration of GNSS into the Indonesia Tsunami Early Warning System (InaTEWS) is therefore recommended to improve the reliability and timeliness of earthquake and tsunami early warning.